Photoswitching proteins: methods and protocols - Cambridge, Sidney (Methods in molecular biology, 2014)
"... focuses on proven applications of photoswitching proteins in cell and neurobiology. Optical approaches have been mostly embraced by the neurosciences to allow fast, high-resolution characterization and manipulation of single cells in complex neuronal tissue. These tools, including photoswitching of proteins, are now successfully used in almost all fields of biological research. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Comprehensive and practical, Photoswitching Proteins: Methods and Protocols highlights many of the possibilities for research based on light-inducible, high-resolution manipulation of biological systems."--P. [4] of cover. --
Includes bibliographical references and index
Keywords: Fotochromie; Proteine